2017
DOI: 10.1128/msystems.00040-17
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Bioinformatics Analysis of Bacillus Genomes Uncovers Conserved Roles of Natural Products in Bacterial Physiology

Abstract: Bacilli are capable of producing a diverse array of specialized metabolites, many of which have gained attention for their roles as signals that affect bacterial physiology and development. Up to this point, however, the Bacillus genus’s metabolic capacity has been underexplored. We undertook a deep genomic analysis of 1,566 Bacillus genomes to understand the full spectrum of metabolites that this bacterial group can make. We discovered that the majority of the specialized metabolites produced by Bacillus spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 65 publications
4
61
0
Order By: Relevance
“…NRPs and PKs-NRPs BGCs in Bacillus species are encoding highly conserved known compounds as well as various novel variants. These findings are consistent with KirK J. Grubbs [64] reported. They found that many of the highly conserved BGCs in Bacillus genomes set encode NRPSs; a few additional PKS-NRPSs, such as zwittermicin and bacillaene, are also well conserved.…”
Section: Disscussionsupporting
confidence: 93%
“…NRPs and PKs-NRPs BGCs in Bacillus species are encoding highly conserved known compounds as well as various novel variants. These findings are consistent with KirK J. Grubbs [64] reported. They found that many of the highly conserved BGCs in Bacillus genomes set encode NRPSs; a few additional PKS-NRPSs, such as zwittermicin and bacillaene, are also well conserved.…”
Section: Disscussionsupporting
confidence: 93%
“…Fengycin, bacillaene, iturin, and difficidin were essentially observed only within the B. subtilis group. This suggests that the different environmental niches inhabited by members of the B. subtilis clade may select for conservation of metabolites with distinct (or potentially redundant) beneficial functions (78). We here describe one such function, that of outcompeting S. plymuthica in nonfavorable growth temperature.…”
Section: Discussionmentioning
confidence: 94%
“…produce different lipopeptide isoforms belonging to the families of surfactins, fengycins or iturins (11). A comparison of predicted BGCs from distinct Bacillus genomes assigned 11 BGCs to B. subtilis strains (12). Notably, a predicted BGC is not proof of the synthesis of the natural product.…”
Section: Introductionmentioning
confidence: 99%